Modern Education in Iran during the Qajar and Pahlavi Periods - Koyagi, Mikiya (History compass, 2009)
Historical writing on modern education in Iran has changed in the past few decades. Earlier works that focused on the top-down feature of modern education were very much influenced by modernization theory, nationalist historiography, and the dichotomous notion of reform and reaction. First, this article suggests that one should analyze the view of specific individuals or groups on modern education rather than simply dividing them into reformists and reactionaries with clear-cut attitudes. Then it surveys the shift from these earlier approaches to new ones that have taken various directions with generally more attention to state-society relations and culture, including such issues as modern education as a site of nation-building and constructing the new social order.